Disseminated cysticercosis: clinical spectrum, Toll-like receptor-4 gene polymorphisms and role of albendazole. Issue 39 (September 2016) - Qavi, Abdul; Garg, Ravindra Kumar; Malhotra, Hardeep Singh; Jain, Amita; Kumar, Neeraj; Malhotra, Kiran Preet; Srivastava, Pradeep Kumar; Verma, Rajesh; Sharma, Praveen Kumar
Abstract : Abstract: In this study, we describe clinical and imaging spectrum, and the natural course of patients with disseminated cysticercosis. How albendazole affects the course of disease has also been evaluated. We assessed the Toll-like receptor-4 gene polymorphisms, to know the reason for the apparently higher prevalence of disseminated cysticercosis in India. Sixty consecutive patients with disseminated cysticercosis were enrolled. Sixty age-and-sex-matched healthy controls were also enrolled for the purpose of genetic study. Twenty patients, who gave consent, were treated with albendazole along with corticosteroids. Forty patients did not give consent for antiparasitic therapy. Assessment for Toll-like receptor-4 gene polymorphisms ( Asp299Gly and Thr399Ile genes) was done. Patients were followed for 6 months. We also performed a literature search of cases published in English language using PubMed electronic database and analyzed 56 cases thus available. There was an increased risk (6.63 fold and 4.61 fold) of disseminated cysticercosis in the presence of Asp299Gly and Thr399Ile polymorphisms in Toll-like receptor-4, respectively. The allelic frequency of Gly (11% vs. 3%, P = 0.024, odds ratio [OR] = 3.52) and Ile alleles (11% vs. 2%, P = 0.009, OR = 4.738) in disseminated cysticercosis was high. Albendazole resulted in complete disappearance of all cerebral lesions in 35% (7/20) patients and reduction in lesion load in remaining 65% (13/20) patients. No significant change in number of cysticercal lesion was noted in patients who did not receive albendazole. No major adverse reaction following antiparasitic treatment was noted. Three deaths were recorded in patients who did not receive antiparasitic treatment. Of the 56 cases reported in PubMed, 33 patients received antiparasitic treatment with follow-up data available for 31 patients. Most (24) of these patients received albendazole. A significant clinical and/or imaging improvements, on follow up, were observed in 27 patients. Of the 4 deaths recorded, 3 had a heavy parasitic load and died after praziquantel therapy. Toll-like receptor-4 gene polymorphisms are associated with an increased susceptibility to disseminated cysticercosis, in the Indian population. Albendazole treatment seems to reduce the lesion load and improve symptoms. Abstract : Supplemental Digital Content is available in the text